2022
DOI: 10.1002/pc.26638
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of damage tolerance of bolted composite structures via “bearing‐after‐impact” tests

Abstract: Although bolted composite joints are mainly designed to resist bearing loading, dynamic loading such as low‐velocity impact can also be a severe threat because of its potential to reduce joint reliability. Surprisingly, it is still unclear how bolted composite joints perform after the dynamic loading, and its effect on the damage tolerance is unknown likewise. This study aims to evaluate experimentally the bearing‐after‐impact (BAI) damage tolerance of bolted glass‐fiber (GF) reinforced epoxy composite joints.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Previous works have indicated that the reinforcement of HNT in multi‐scale composite specimens restricts matrix cracks, delamination, and fiber breakage damages created under impact loads. [ 20,35,36,39 ] Impact damage formations are constrained by toughening mechanisms of HNTs such as crack pinning and deflection, particle debonding and bridging. [ 35 ] In nanoclay addition to epoxy, the widely used reinforcing element of the clay family, improvements were also obtained for impact load performance of glass fiber composites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have indicated that the reinforcement of HNT in multi‐scale composite specimens restricts matrix cracks, delamination, and fiber breakage damages created under impact loads. [ 20,35,36,39 ] Impact damage formations are constrained by toughening mechanisms of HNTs such as crack pinning and deflection, particle debonding and bridging. [ 35 ] In nanoclay addition to epoxy, the widely used reinforcing element of the clay family, improvements were also obtained for impact load performance of glass fiber composites.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the intensity of oscillations is related closely to the type of impact damage. [ 20,41 ] Moreover, the slope from the initial point to the peak point on curves is demonstrated the flexural rigidity of specimens. Accordingly, the multi‐scale composite laminates have higher flexural rigidity than GFRP specimens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–3 ] The laminated construction of fiber‐reinforced composites and the characteristics of their constituent properties (fiber and matrix) often make their structural performance sensitive to even transverse impact loading. [ 4–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Fiber‐reinforced polymers (FRPs) have been extensively used in strategic industries, including aeronautical, marine, transportation, and renewable energy. [ 1–6 ] During their service life, FRPs are subjected to severe environmental conditions such as moisture and elevated temperatures, reducing their performance. [ 1,7–10 ] “Aging” is referred to as the process of degrading the properties of materials over time due to environmental conditions.…”
Section: Introductionmentioning
confidence: 99%